2005
DOI: 10.2980/i1195-6860-12-1-27.1
|View full text |Cite
|
Sign up to set email alerts
|

Haematological variables are good predictors of recruitment in nestling pied flycatchers (Ficedula hypoleuca)

Abstract: Abstract:The number of different types of circulating leucocytes may provide information about the health state of birds in the wild. We counted the number and proportions of circulating leucocytes in blood smears of nestling pied flycatchers (Ficedula hypoleuca) shortly before fledging. We studied the relationship between these haematological measures and environmental factors like parasitism, body mass, hatching date, and brood size. The heterophils-to-lymphocytes ratio was higher in nestlings whose nests su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 56 publications
8
96
1
1
Order By: Relevance
“…Repeatability scores of our counts were highly significant (H/Ly ratio F 91,92 =8.28, P<0.01, intraclass correlation coefficient=0.78; Lessells and Boag, 1987). A high H/Ly ratio is often interpreted as a sign of physiological stress Lobato et al, 2005;Campbell and Ellis, 2007) and, for example, sustained flight has been shown to increase the H/Ly ratio (Matson et al, 2012).…”
Section: Laboratory Analysesmentioning
confidence: 84%
“…Repeatability scores of our counts were highly significant (H/Ly ratio F 91,92 =8.28, P<0.01, intraclass correlation coefficient=0.78; Lessells and Boag, 1987). A high H/Ly ratio is often interpreted as a sign of physiological stress Lobato et al, 2005;Campbell and Ellis, 2007) and, for example, sustained flight has been shown to increase the H/Ly ratio (Matson et al, 2012).…”
Section: Laboratory Analysesmentioning
confidence: 84%
“…H/L ratios have been used to assess susceptibility to disease and infection (e.g., Davis et al 2004;Al-Murrani et al 2006) and to indicate immune challenge ). These ratios are also known to be affected by growth and reproduction (e.g., Moreno et al 2002;Lobato et al 2005). The use of eosinophil counts as an indicator of stress is not as common, although studies have demonstrated that stress-induced glucocorticoid secretion leads to a reduction in eosinophil numbers in mammals (Gordon 1955) and amphibians (Belden and Kiesecker 2005).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…Golet et al 2000, Kitaysky et al 2001b, Kitaysky et al 2003) and a subsequent increase in H:L ratio (e.g. Hoi-Leitner et al 2001, Suorsa et al 2004, Lobato et al 2005.…”
Section: Introductionmentioning
confidence: 99%